Origin of nuclear and chromosomal alterations derived from the action of an aneugenic agent-Trifluralin herbicide - Casimiro Fernandes, Thais Cristina [UNESP]; Christofoletti Mazzeo, Dania Elisa [UNESP]; Marin-Morales, Maria Aparecida [UNESP] (Academic Press Inc. Elsevier B.V., 2009)
Trifluralin is a herbicide capable of interfering in mitotic cell division due to either microtubule depolymerization or alteration in the concentration of calcium ions within the cell. The aim of this study was to investigate the effects of trifluralin in Allium cepa meristematic cells, evaluating the induction mechanisms of the chromosomal and nuclear aberrations. In this study, A. cepa root tips were submitted for 24 h treatment to several concentrations of this herbicide and 48 h recovery post-treatment. The results showed that some concentrations of trifluralin can lead to a mitotic index inhibition, besides inducing chromosomal and nuclear alterations throughout the mitotic cycle. Some of the alterations found seem to be resulting from the herbicide action in different phases and in more than one consecutive cell cycle. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Allium cepa; Aneugenic; Supernumerary microtubule-organizing center; Mitosis